MENEMUKAN KEMBALI PEMBARUAN PERKOTAAN BERBASIS PENGEMBANGAN MASYARAKAT: STUDI PENANGANAN PEMUKIMAN KUMUH DI PERKOTAAN INDONESIA - Muhammad Taufiq; Petrus Natalivan Indradjati; Suhirman Suhirman; Benedictus Kombaitan (Diponegoro University, 2019)
The urban renewal concept is one of the city development policies approaches. It promotes profit optimization in urban areas. However, this is done by eroding existing slums and ending with injustice for the community. For this reason, city development policies need to direct urban renewal implementation based on community development. The question arises whether urban renewal needs to be applied for urban areas in Indonesia, whether urban renewal brings certain benefits in achieving a more humane society development and its limits. This article aims to provide a theoretical understanding of the considerations and implications for its application through illustrative case studies from several major cities in Indonesia. This study evaluates urban renewal ideas from a community development viewpoint, through descriptive, evaluative analysis and literature. Study results show that urban renewal is necessary for cities in Indonesia in terms of policies that make the city center become a more competitive business area and generate maximum urban profits through tax revenues. On the other hand, this is done to beautify the city's face, which will automatically improve community development in cities and suburbs. Local wisdom in the context of a city's development policy choice base is a limitation for its implementation optimality.